Fiscal Rules at a Glance : Country Details from a New Dataset - Budina, Nina (IMF Working Papers; Working Paper ;, 2012)
This paper provides country-specific information on fiscal rules in use in 81 countries from 1985 to end-September 2012. It serves as background material and update of the July 2012 Working Paper 'Fiscal Rules in Response to the Crisis-Toward the 'Next Generation' Rules: A New Dataset' and is also available in an easy accessible electronic data visualization tool (http://www.imf.org/external/datamapper/FiscalRules/map/map.htm.).The dataset covers four types of rules: budget balance rules, debt rules, expenditure rules, and revenue rules, applying to the central or general government or the public sector. It also presents details on various characteristics of rules, such as their legal basis, coverage, escape clauses, as well as key supporting features such as independent monitoring bodies.